Particle Production in Heavy Ion Collisions at Intermediate Energies - Prassa, V.; Gaitanos, T.; Wolter, H. H.; Lalazissis, G. A.; Di Toro, M. (HNPS Advances in Nuclear Physics, 2020)
We investigate the influence of the in-medium modifications of nucleon-nucleon cross sections on the particle production in heavy ion collisions at intermediate energies. In particular, it is shown that the pion and kaon yields and their rapidity distributions are strongly affected by the density dependence of the inelastic cross sections. On the other hand, the particle ratios depend less on the in-medium behavior of the inelastic cross sections.